PENGARUH WORK FAMILY CONFLICT TERHADAP JOB INVOLVEMENT STUDI PADA PERAWAT DAN BIDAN RSU X DALAM RANGKA MENINGKATKAN PERFORMA KERJA - Prasetyo, Mieke; Ardiwinata, Maya Rosmayati; Yanuarti, Nurul (Universitas Muhammadiyah Jember, 2019)
Married nurses and midwives have double roles not only as an employee but also as a wife and a mother. Responsobilities on both roles have different characteristics. Their effort to fulfill each responsibility at the same time may cause conflicts. These work family confict may occur in some types, such as times based conflict, strain based conflict, and behavior based conflict. The consequences of the conflict occured will affect their jobs. The conflicts occured will affect nurses and midwives involvement in completion their assignments at hospital. Nurses and midwives who able to identify theirself on their job will result in their optimal work performance at hospital.The study aims to discover whether there is an effect of Work Family Conflict on Job Involvement on nurses and midwifes at RSU X. Data collection on work family conflict variable based on modified and validated instrument from S. Carlson et.al (2000), and for job involvement variable based on modified quetionnaire from Lodhal dan Kejner (1965). Participants of the study were 65 respondents with characteristics such as woman, merried, and have a child.Result of this study was work family conflicts, both in times based conflict, strain based conflict, and behavior based conflict, did not significantly effecting job involvement on nurses and midwives at RSU X. It showed that role conlicts on participants did not influence nurses and midwives involvement in completion of their assignments.